1978
DOI: 10.1055/s-0028-1104828
|View full text |Cite
|
Sign up to set email alerts
|

Das Tetracyclin-Ulkus der Speiseröhre

Abstract: During treatment with doxycycline capsules three patients (aged 24, 34, and 39 years, respectively) developed acute oesophageal ulcers with dysphagia as the cardinal symptoms. They became symptom-free and the ulcers healed promptly on symptomatic treatment. In-vitro experiments in rats indicated that doxycycline accumulates within the erythrocyte membrane and epithelial cells of the oesophagus. This accumulation is followed by cell destruction. It is assumed that doxycycline capsules remain within the oesophag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

1980
1980
2012
2012

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(4 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…Direct irritant effect of medication due to prolonged contact with esophageal mucosa appears to be the most likely factor. However, the acidic nature of some medications such as tetracycline hydrochloride and its derivatives [3,7,[15][16][17][18], ascorbic acid [81, and ferrous sulfate [6] may also play a role. Slow clearance of the medication due to the large size of the tablet or abnormal esophageal motility may contribute to prolonged contact between the ingested medication and the esophageal mucosa.…”
Section: Discussionmentioning
confidence: 99%
“…Direct irritant effect of medication due to prolonged contact with esophageal mucosa appears to be the most likely factor. However, the acidic nature of some medications such as tetracycline hydrochloride and its derivatives [3,7,[15][16][17][18], ascorbic acid [81, and ferrous sulfate [6] may also play a role. Slow clearance of the medication due to the large size of the tablet or abnormal esophageal motility may contribute to prolonged contact between the ingested medication and the esophageal mucosa.…”
Section: Discussionmentioning
confidence: 99%
“…Doxycycline 0.1 g, ferrosulfate 0.1 g, ferrosuccinate 0.075 g and the analgesic combination drug Doleron®, were found to have a pH less than 3 (3). Other authors have also reported on the acidity of a doxycycline solution as a plausible explanation for the tissue damage (1,12). Solutions of pH less than 1.6 produce esophagitis in the cat (13), whereas a pH less than 3 is considered to be corrosive in the human esophagus (2).…”
Section: Discussionmentioning
confidence: 99%
“…In one study 100 severe esophageal ulcerations and 14 high esophageal strictures were attributed to oral drugs in a population of 1 million people (4). In the literature, 80-90% of patients with drug-induced esophageal lesions revealed no history of previous swallowing difficulties (3,4,9,10,12,14,23).…”
Section: Introductionmentioning
confidence: 99%
“…Die Azidität der Tetrazykline ist ein anderer wesentlicher schädigender Aspekt [2]. Versuche mit Ratten zeigten, dass Doxycyclin im Stratum basale des Plattenepithels akkumuliert und schlieûlich zu einer Störung der Proteinsynthese und Zelldegeneration führt [7].…”
Section: Klinischer Untersuchungsbefundunclassified